2020
DOI: 10.14264/a27f782
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Volume Fraction on Turbulence in Pipes and Channels

Abstract: It is well known that turbulent channel and pipe flows show subtle differences in flow statistics. Here we investigate the effect of particle loading on the turbulence in these two geometries. We perform direct numerical simulations of both turbulent channels and pipes at Re τ = 180 with St + = 100 particles. Particle volume fractions of Φ f = 2×10 −5 , 2×10 −6 are compared with unladen simulations. Mean flow and turbulence intensities as well as energy spectra are computed along with visual inspection of Q-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Further, when point-particle direct numerical simulation (PP-DNS) of pipes (Picano, Sardina & Casciola 2009) is compared with channels (Sardina et al 2012), an augmentation of near-wall particle concentration for pipes is observed. This greater wall accumulation for pipes was directly contrasted by Zahtila et al (2020), suggesting that the two geometric distinguishing features of a pipe, an axisymmetric restriction on centreline and curvature in the solid surface at the wall, are not negligible. A pipe was chosen for this study to maintain intimate connection with the preceding deposition experiments and applied mathematical modelling.…”
Section: Introductionmentioning
confidence: 97%
“…Further, when point-particle direct numerical simulation (PP-DNS) of pipes (Picano, Sardina & Casciola 2009) is compared with channels (Sardina et al 2012), an augmentation of near-wall particle concentration for pipes is observed. This greater wall accumulation for pipes was directly contrasted by Zahtila et al (2020), suggesting that the two geometric distinguishing features of a pipe, an axisymmetric restriction on centreline and curvature in the solid surface at the wall, are not negligible. A pipe was chosen for this study to maintain intimate connection with the preceding deposition experiments and applied mathematical modelling.…”
Section: Introductionmentioning
confidence: 97%